Jesus and the Continuing Exile of Israel in the Writings of N.T. Wright - Bird, Michael F. (Journal for the study of the historical Jesus, 2015)
N.T. Wright’s thesis that the historical Jesus conducted his prophetic career in the context of a widespread belief that Israel was in a protracted state of exile has courted much controversy. This study sketches Wright’s articulation of the return-from-exile theme in Jewish literature, describes some of the scholarly criticisms to this view, and defends a chastened view of Wright’s thesis that return-from-exile remains a useful category for understanding Judaism and Jesus even if it does not necessarily carry the meta-narratival freight that Wright attributes to it.